Peningkatan Penalaran Siswa Dalam Pembelajaran Matematika Menggunakan Pendekatan Induktif (Ptk Pada Siswa Kelas Vii Smp Negeri 1 Kedunggalar Semester Ganjil Tahun 2015/2016) - 'ILMAN NAFI'AH, PUTRI (2016)
The purpose of this research is to improve students's reasoning in mathematics learning using an inductive approach. This research is a classroom action research. The subject of recipient action in this study were VII C grade students of Secondary School 1 Kedunggalar, while the subject of implementing measures is a mathematics teacher. The implementation of action class was performed for two cycle, four meetings. The data was collected by observation, documentations, test methods and field notes. To insure the validity of data it used triangulation of source and triangulation of techniques. The technique of analysis data used by reduction of data, presentasion of data and verification of data. The results showed an increasing of students learning mathematics reasoning using inductive approach seen from the percentage of: (1) the student is able to forward allegations from 8,57% up to 71,43%; (2) the student is able to perform mathematical manipulations from 28,57% up to 77,14%; (3) the student is able to appeal conclusions from 14,28% up to 74,28%; (4) the student is able to explain from 8,57% up to 71,43%. It can be concluded that the application of inductive approach in teaching mathematics can improve students's reasoning.